The Crown of Thorns: A Token for the Sorrowing - Chapin, E. H. (Edwin Hubbell), 1814-1880 (Salt Lake City, UT : Project Gutenberg, 1999)
"The Crown of Thorns: A Token for the Sorrowing" by E. H. Chapin is a collection of religious discourses written during the mid-19th century. The work offers profound reflections on suffering, hope, and the Christian perspective on sorrow, aiming to provide consolation for those in distress. The author shares personal experiences, particularly stemming from the loss of a loved one, which lend an emotional depth to the themes explored in these writings. At the start of the book, the preface introduces the context in which the discourses were written, highlighting the author$1 (Bs own grief and the desire to offer sympathy to others facing their sorrows. The opening section begins with the discourse titled "The Three Tabernacles," which reflects on the desire to cling to moments of joy and the natural human inclination to seek permanence in transient experiences. Chapin discusses the lessons derived from Peter$1 (Bs longing to build tabernacles during the Transfiguration, emphasizing the need to embrace the challenges of life and endure suffering as part of a spiritual journey toward deeper understanding and connection with God. Overall, the initial portion sets the stage for an exploration of sorrow's role in personal growth and the pursuit of faith. (This is an automatically generated summary.)s
The three tabernacles -- The shadow of disappointment -- Life a tale -- The Christian view of sorrow -- Christian consolation in loneliness -- Resignation -- The mission of little children -- Our relations to the departed -- The voices of the dead -- Mystery and faith.
Release date is 1999-11-01
Produced by An Anonymous Volunteer, and David Widger
Keywords: Consolation